The significance of the land in the education and health of Anishinaabe youth from Pic River First Nation - Richmond-Saravia, Michelle (2012)
This study shares the experiences of twenty-one Anishinabek youth from Pic River First Nation, Ontario, Canada in relation to how the Land is significant for their education and good health. This thesis is meant as a small part of my family's role in protecting the Land; my upbringing and connections to my Anishinabek community have influenced my desire to learn about traditional education and its role in supporting Anishinabek learners. Understanding the significance of the Land for Anishinabek youth and what they see as its connection to their education and health is important. These findings support the position that we should continue to keep the Land the way it is so our future generations can experience this too. This research study contributes to the need to hear from Indigenous youth. The stories shared here reflect how Pic River youth situate themselves and thrive from the Land, community and family in Pic River. Though there is research on Indigenous ways of knowing, and how Indigenous youth learn, there are fewer studies on how Land is significant for the youth, how the Land makes them feel, and how this contributes to their education and good health. In my findings, I heard that "the Land is everything." Miigwetch in sharing this journey with me.